2009
DOI: 10.1158/0008-5472.can-08-4786
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cδ Activates RelA/p65 and Nuclear Factor-κB Signaling in Response to Tumor Necrosis Factor-α

Abstract: Nuclear factor-KB (NF-KB) is tightly modulated by IKB kinases and IKBA in the cytoplasm. On stimulation, NF-KB translocates into the nucleus to initiate transcription; however, regulation of its transcriptional activity remains obscure. Here, we show that protein kinase C (PKC) D controls the main subunit of NF-KB, RelA/p65. On exposure to tumor necrosis factor-A (TNF-A), the expression of RelA/ p65 target genes such as IKBA, RelB, and p100/p52 is upregulated in a PKCD-dependent manner. The results also show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…In HEK293 and U2OS cells, PKC␦ forms complexes with p65 in the nucleus following TNF␣ exposure. The PKC␦-p65 complex is believed to occupy NF-B target gene promoters and orchestrate RelA/p65 transactivation (14). Our study revealed another mechanism that involves a cytosol-specific PKC␦-p65 interaction that is independent of the IB pathway.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In HEK293 and U2OS cells, PKC␦ forms complexes with p65 in the nucleus following TNF␣ exposure. The PKC␦-p65 complex is believed to occupy NF-B target gene promoters and orchestrate RelA/p65 transactivation (14). Our study revealed another mechanism that involves a cytosol-specific PKC␦-p65 interaction that is independent of the IB pathway.…”
Section: Discussionmentioning
confidence: 65%
“…Consistent with this hypothesis, overexpression of the catalytic fragment in the absence of an apoptotic stimulus was sufficient to induce apoptosis in a variety of cell types (10). In contrast, several lines of studies showed a pivotal role for PKC␦ in antiapoptotic function in response to cytokines including tumor necrosis factor-␣ (TNF␣) (14). Silencing PKC␦ expression by siRNA resulted in inhibition of TNF-mediated extracellular signal-regulated kinase 1/2 activation (15).…”
mentioning
confidence: 86%
“…Previous studies have showed that activation of different PKC isoforms results in NF-kB activation. [41][42][43] It has been reported that, in embryonic mouse stem cells, Shh enhances the translocation of PKCa, d, and z isoforms from the cytosol to the cytoplasmic membrane supporting Hh-induced activation of these PKC isoforms. 31 Earlier studies have found that CARMA3 and TRAF6 are required for GPCR-induced NF-kB activation in Mef cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PKC-delta by other stimuli (e.g., thrombin, bryostatin, and tumor necrosis factor alpha [TNF-␣]) is also sufficient to drive the NF-Bdependent transcription of cellular genes (ICAM-1, interleukin-8 , and RelA/p65) in human endothelial, epithelial, and osteosarcoma cells (5,32,43). In HFF, smooth muscle cells, endothelial cells, and monocytes, HCMV infection rapidly results in NF-B translocation to the cell nucleus and NF-B binding to the B site in DNA, regardless of the HCMV strain tested.…”
mentioning
confidence: 99%